Virtual advertising and brand awareness. (2nd August 2006) - Cianfrone, Beth; Bennett, Gregg; Siders, Ron; Tsuji, Yosuke
The purpose of this study was to analyse the effectiveness of virtual advertising on consumer memory of brand sponsorship. More specifically, we sought to compare the capacity of consumers to identify brand sponsors virtually inserted within a televised sporting event to their ability to remember conventional television commercial sponsors. A 40-minute segment of a televised broadcast of a Southeastern Conference (SEC) football game, complete with television commercials and virtual advertisements, was the means of study used to assess the effectiveness of the different forms of advertising in terms of brand sponsorship identification. The findings suggest differences between spectator identification of virtual ads and television commercials on consumer memory. Management and marketing implications are discussed. This exploratory study serves as a foundation for further research on the effectiveness of virtual advertising and additional research streams are proposed.